Os fatores chave do alinhamento estratégico interno no Tribunal de Contas do Estado do Ceará - Nascimento, Carlos Alberto de Miranda (2018)
The lack of evaluation of public services allied with the decline of the confidence in the institutions indicates that the absence of effectiveness of public organizations may be related to the lack of measurement systems capable of identifying the existence of the necessary conditions to achieve the objectives set by the institutions. In this context, this study aimed to investigate, according to the perception of the public servants, the presence of key factors for the internal strategic alignment of organizations in the Tribunal de Contas do Estado do Ceará. For this, a descriptive and quantitative study was used in the research unit, which verified, through a questionnaire, the perception of 224 public servants about the presence of key factors for strategic alignment in organizations. The result allowed to evaluate the organization for vertical and horizontal alignment, due to the analysis of five factors: Strategy Formulation (SF), People's Involvement with Strategy (PIS), Management Capacities for Strategy Implementation (MCSI), Process Orientation (PO), and Citizens Orientation (CO). It was concluded that, according to respondents' perception, there is no internal strategic alignment in the institution, which is why it is recommended to the researched institution, among other measures, the planning and execution of practices that encourage communication between Senior Management (Directors) and Operational (Servers), in particular as regards the development of the unique sense of direction necessary for organizations to focus their efforts on achieving common goals. Finally, it is envisaged in future research to develop a methodology of measuring the results that allows the classification of the presence of factors at maturity levels, to diagnose the degrees of evolution to which public organizations can still evolve.